2023
DOI: 10.1038/s41598-023-27535-1
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite density and detailed qualitative microscopy enhances large-scale profiling of infection endemicity in Nigeria

Abstract: With global progress towards malaria reduction stalling, further analysis of epidemiology is required, particularly in countries with the highest burden. National surveys have mostly analysed infection prevalence, while large-scale data on parasite density and different developmental forms rarely available. In Nigeria, the country with the largest burden globally, blood slide microscopy of children up to 5 years of age was conducted in the 2018 National Demographic and Health Survey, and parasite prevalence pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Here, we estimate a 100-fold higher parasite density when measured by microscopy compared to densities measured by qPCR, consistent with similar trends observed in previous studies [55]. The findings of this study also indicate that the false-negative rate of microscopy decreases with increasing parasite density, a pattern observed in other studies too [81].…”
Section: Discussionsupporting
confidence: 92%
“…Here, we estimate a 100-fold higher parasite density when measured by microscopy compared to densities measured by qPCR, consistent with similar trends observed in previous studies [55]. The findings of this study also indicate that the false-negative rate of microscopy decreases with increasing parasite density, a pattern observed in other studies too [81].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, states with the highest number of urban clusters reporting zero test positivity rates included Lagos, Rivers, and Abia. Interestingly, prior research has documented low malaria infection rates, as determined by microscopy, in urban Lagos, with rates as low as 8% and 0.9% [45][46][47][48]. However, it remains somewhat unclear why lower test positivity rates were observed in the urban clusters of Rivers and Abia, especially when previous studies conducted in urban areas have indicated higher test positivity rates among the study populations [49][50][51].…”
Section: Discussionmentioning
confidence: 93%
“…The observed differences might be due to a longer duration of fever or more severe cases in this study population, as the study site was a malaria referral hospital. Moreover, the study identified a slightly higher gametocyte density compared to Nigerian paediatric patients [ 49 ], possibly attributed to the higher malaria endemicity in sub-Saharan Africa. The presence of acquired immunity to malaria [ 50 ] might contribute to a decrease in gametocyte density.…”
Section: Discussionmentioning
confidence: 99%